Scientific Exegesis and Epistemic Boundaries: A Qualitative Study of Tafsir al-Muntakhab on Qur’anic Cosmology - Munir, Misbahul; Surahmat (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
The development of modern science, particularly in cosmology and natural sciences, has created epistemological tensions in Qur’anic studies. Scientific exegesis (tafsīr ʿilmī) has emerged as an approach linking revelation with empirical knowledge, yet it often faces criticism for potentially reducing divine revelation to positivistic frameworks. Tafsir al-Muntakhab, compiled by the Lajnah al-Qur’an wa al-Sunnah under the Supreme Council for Islamic Affairs in Egypt, occupies a unique position as an institutional tafsir designed for modern readers. This study analyzes the construction and epistemological legitimacy of scientific interpretation in Tafsir al-Muntakhab, focusing on QS. Al-Anbiyāʾ [21]:30 and QS. Adz-Dzāriyāt [51]:47. A qualitative design employing content analysis and hermeneutic interpretation was used, emphasizing textual fidelity and contextual understanding. Findings show that Tafsir al-Muntakhab separates core Qur’anic meanings from supplementary scientific explanations, positions science as an illustrative tool, and balances textual, scientific, and contemporary reader needs. Analysis of cosmological verses reveals understanding of the initial union and separation of heaven and earth, planet formation, emergence of life from water, and cosmic expansion, consistent with modern scientific theories. This approach reflects a moderate scientific tafsir that preserves the epistemic authority of the Qur’an while facilitating constructive dialogue between revelation and science.